2012
DOI: 10.1016/j.jsbmb.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin and hormone therapy effects on APOE mRNA expression in hypercholesterolemic postmenopausal women

Abstract: Menopause is associated with changes in lipid levels resulting in increased risk of atherosclerosis and cardiovascular events. Hormone therapy (HT) and atorvastatin have been used to improve lipid profile in postmenopausal women. Effects of HT, atorvastatin and APOE polymorphisms on serum lipids and APOE and LXRA expression were evaluated in 87 hypercholesterolemic postmenopausal women, randomly selected for treatment with atorvastatin (AT, n=17), estrogen or estrogen plus progestagen (HT, n=34) and estrogen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…As reported by previous studies, we found an association of APOE *2 allele with lower risk for hypercholesterolemia (OR: 0.27, CI95%; 0.01-0.85, p=0.025) (Cerda et al, 2011b). Interestingly, APOE *3*3 genotype carriers had greater reduction of APOE mRNA levels in PBMC after atorvastatin treatment (Issa et al, 2012). Another study investigated the APOE g.4798T>G in subjects with statin-controlled dyslipidemia and did not find association with oxidative stress biomarkers and plasma tocopherol (Botelho et al, 2012).…”
Section: Lipid Metabolism-related Genessupporting
confidence: 84%
See 1 more Smart Citation
“…As reported by previous studies, we found an association of APOE *2 allele with lower risk for hypercholesterolemia (OR: 0.27, CI95%; 0.01-0.85, p=0.025) (Cerda et al, 2011b). Interestingly, APOE *3*3 genotype carriers had greater reduction of APOE mRNA levels in PBMC after atorvastatin treatment (Issa et al, 2012). Another study investigated the APOE g.4798T>G in subjects with statin-controlled dyslipidemia and did not find association with oxidative stress biomarkers and plasma tocopherol (Botelho et al, 2012).…”
Section: Lipid Metabolism-related Genessupporting
confidence: 84%
“…APOE alleles did not influence plasma lipids after long term treatment with simvastatin (Fiegenbaum et al, 2005b) and short term treatment with atorvastatin (Cerda et al, 2011b). We also reported no association between APOE genotypes and lipid-lowering response to atorvastatin combined or not with hormonal therapy for three months in postmenopausal HC women (Issa et al, 2012). As reported by previous studies, we found an association of APOE *2 allele with lower risk for hypercholesterolemia (OR: 0.27, CI95%; 0.01-0.85, p=0.025) (Cerda et al, 2011b).…”
Section: Lipid Metabolism-related Genesmentioning
confidence: 47%
“…However, these side effects do not exceed the benefits promoted by the hypercholesterolemia therapy [ 14 , 15 ]. More importantly, even postmenopausal patients show a significant reduction of atherosclerosis after being treated with statins [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, researchers have reported their attempts to combine genetic variants with different aspects of menopausal syndromes [ 3 , 5 , 6 , 32 ]. We selected two genes in our study: one for APOE and one for LEP , on the basis of biological conditions mentioned in [ 33 , 34 , 35 , 36 , 37 , 38 ] to be associated with menopause.…”
Section: Discussionmentioning
confidence: 99%
“…et al [ 36 ], in their study of APOE3 , suggest that obesity or metabolic syndrome risk should be effectively managed in APOE3 isoform groups to reduce serum LDL in postmenopausal Korean women. In a different study, Issa et al [ 37 ] found that menopause is associated with changes in lipid levels, resulting in an increased risk of atherosclerosis and cardiovascular events. They noticed that medication used to lower the level of cholesterol (Atorvastatin) downregulates the APOE mRNA expression and is modified by APOE genotypes in peripheral blood mononuclear cells from postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%